Construct Validity And Reliability Of Outdoor Education Evaluation Instrument - Hashim, Assoc. Prof Dr Ahmad; Alvin Raj, Alvin (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to obtain the validity and reliability of a survey instrument to evaluate outdoor education. It is a survey which is divided into three components namely first; strategic knowledge, second; efficient behaviour and third; affective. Development of the survey instrument is based on Tennessee Self Concept Questionnaire, Multifactor Leadership Questionnaire (MLQ), Participant Motivation Questionnaire (PMQ), Cooper Smith Inventory, Group Environment Questionnaire (GEQ) and Outdoor Education Manual (MPL). There are 95 items prepared based on the five-point Likert scale which were tested at the pilot test level. It involved 100 research subjects aged between 15 and 16 years old who were selected based on purposive random sampling.  In addition, the research method applied is in the form of pre-experimental one group pre-test–post-test. Results of the analysis showed that overall field expert validity is r = .89 and language expert validity is r = .90, while the Cronbach alpha reliability correlation value of outdoor education instrument evaluation survey is  r = .89. Next, this survey was tested again for construct validity using the factor analysis method for statistical analysis  which would validate each item tested was supposed to be in the right component.  From the analysis, results show that Bartlett’s test is significant p < .05 and Kaiser-Meyer-Olkin index range is r = .62. 81.16 percent variant is explained from  18 components which have been analyzed with more than one eigenvalue. 51 survey items are produced out of 95 items of the survey based on this factor analysis method. Research has shown that the survey instrument developed  is valid and reliable to be used for Sabah’s Co-curricular Centre.